The Quality of the System and the Behavior of Muzaki in Non-Cash Zakat Payments: The Case of Baznas Pekanbaru, Indonesia - Suprapto, Lelik; Lisman, Muhammad; Septianingsih, Rika (MD Research Center, 2025)
This study aims to analyze the impact of the quality of non-cash zakat payment systems on the behavior of muzaki in fulfilling their zakat obligations through digital platforms at Baznas Pekanbaru. Non-cash zakat payments have become a more practical alternative, but muzaki participation in Pekanbaru is still relatively low. This research uses a quantitative approach, collecting data through questionnaires distributed to 40 muzaki who use the non-cash zakat payment system. Validity and reliability tests were conducted to ensure the quality of the data, while linear regression analysis was used to examine the relationship between system quality (ease of use, security, and service quality) and muzaki behavior. The results indicate that system quality has a significant and positive impact on muzaki behavior. The regression coefficient of 0.640 suggests that each 1% improvement in system quality can increase muzaki behavior by 64%. The T-test shows a significance value of 0.000, indicating that system quality significantly influences the decision of muzaki to use digital platforms for zakat payments. Therefore, this study recommends that Baznas Pekanbaru continue to improve the quality of the non-cash zakat payment system and carry out socialization and education for the public to increase muzaki participation. This study also suggests that future research should consider a larger sample size and varying methods to obtain more comprehensive results.